2022-RA-721-ESGO Clinical outcomes of SBRT boost to the cervix as an alternative to intracavitary brachytherapy in locally advanced cervical cancer: Retrospective analysis from the West of Scotland. (20th October 2022) - Amali, Nasibah Kharul; Sadozye, Azmat; Morris, Susan; Harrand, Rosie; Hunter, Bianca; Kerr, Ashleigh; Graham, Kathryn
Abstract : Introduction/Background: Concurrent chemoradiotherapy (CCRT) combined with image guided brachytherapy (IBGT) is the international gold standard management for locally advanced cervical cancer. ESTRO guidelines recommend aiming for EQD2 of 85–90Gy to the cervix, in order to achieve local control rate of >90%. Associated G3–5 morbidity is up to 5–10%, with fistula incidence <5%. However, a proportion of patients are ineligible for IGBT and a standard photon boost is suboptimal. We evaluated the indications for SBRT boost at our institution and the resultant local control/toxicity outcomes. Methodology: The central radiotherapy prescribing system at a single institution was interrogated to identify patients with locally advanced cervical cancer who received SBRT boost to cervix in addition to or as a replacement for IBGT, from 1st July 2017 to 31st January 2021. Results: 17 patients were identified; median age was 68 years (range 32–77) and median follow up was 17 months. FIGO 2009 stage distribution was II (8/17), III (7/17), and IV (2/17). Mean tumour size was 4.5 cm. Indication for SBRT consisted of: medical contra-indication (9/17), unfavourable anatomy (5/17), and patient refusal (3/17). Median dose of external beam was 45Gy in 25 fractions (range 43–50Gy). SBRT boost PTV was delineated on CT (cervix and gross residual disease with a 4–5 mm margin), aiming for 24–28Gy in 4 fractions (range 7–28Gy). Median cumulative EQD2 (a/β= 10) was 75.2Gy (range 58–91), and median SBRT PTV size was 54 cm 3 (range 12–126). Local control rate was 15/17 (88.2%). G3 toxicity occurred in 2/17 (11.8%); one rectovaginal-vaginal and one vesico-vaginal fistula (the latter had progressive disease). No G4–5 toxicity was reported. Conclusion: SBRT boost was effective and tolerable in this cohort, but EQD2 of 85–90Gy was not achieved in majority of cases. MRI based planning may improve target delineation and a consensus guideline on appropriate constraints would be advantageous.